SINO-VIETNAMESE PEOPLE’S ECONOMIC ACTIVITIES IN DISTRICTS 5, 6, AND 11 OF HO CHI MINH CITY, VIETNAM (1996-2016) - Ha, Trieu Huy (Trường Đại học Đà Lạt, 2023)
This article clarifies the involvement of the Sino-Vietnamese people in Ho Chi Minh City’s economy from 1996 to 2016. Vietnam has accelerated the process of industrialization and modernization since 1996, and Ho Chi Minh City now has a thriving local economy. As with other ethnic groups, the Sino-Vietnamese people have made a considerable contribution to boosting the local economy. Based on the theory of functionalism, culture-economy relationships, and primary anthropological research methods, this article assesses the economic contributions of the Sino-Vietnamese in industry and handicrafts, commerce and services, and finance and credit. However, there are many obstacles for the Sino-Vietnamese economy. The quality of goods is insufficient to meet consumer satisfaction. The harshly competitive market confronts their businesses with numerous challenges. The abandonment of traditional professions by the young Sino-Vietnamese generation poses a threat to traditional businesses, and COVID-19 is a pressing issue for their economy. This article proposes realistic solutions to encourage the Sino-Vietnamese people to overcome disadvantages and contribute to the economy of Ho Chi Minh City in the future.